Tindog, Tacloban! a resilience complex in the strategic hub of Eastern Visayas - Dacquel, Marian Joyce V.
The Philippines is the third most vulnerable country to natural hazards, making it one of the world's disaster-prone countries. The country is also one of the most vulnerable to the effects of climate change. In 2013, Super Typhoon Yolanda, one of the strongest storms ever recorded at landfall, devastated the Eastern Visayas region with its strong winds. Its massive storm surge was even more destructive. Among those cities and municipalities affected by Typhoon Yolanda, Tacloban City suffered the greatest damage to housing and settlements. The project aims to produce an inclusive design of a resilience complex in Tacloban City that can dignify and help the Yolanda survivors and those who are heavily affected by the disaster. Taking that into consideration, the end goal is to provide a design for building facilities that could be addressed by proposing an architectural intervention for Tacloban City's community, disaster, and economic resilience. The project will be located across the proposed Cancabato New Central Business District development. The proposed Tacloban City Resilience Complex shall be an anchor facility, as the City Planning and Development Office (CPDO) envisions the proposed reclamation to raise awareness and involvement among the community.